Answer:
2 irrational solutions
Step-by-step explanation:
using the quadratic formula:
[tex] \frac{ -b \:± \sqrt{b {}^{2} - 4ac } }{2a} [/tex]
3x²−x−5=0
where a = 3, b = -1 and c = -5, plug in those values in the quadratic formula
[tex] \frac{ - ( - 1)±\sqrt{(1) {}^{2} - 4(3)( - 5) } }{2(3)} [/tex]
you get two solutions:
[tex] \frac{1 + \sqrt{61} }{6} \: and \: \frac{1 - \sqrt{61} }{6} [/tex]
both can be written as:
[tex] \frac{1± \sqrt{61} }{6} [/tex]
They are irrational as they cannot be written in the form p/q where p and q are whole numbers (integers)